2012
DOI: 10.1073/pnas.1121500109
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrical roles of zinc fingers in dynamic DNA-scanning process by the inducible transcription factor Egr-1

Abstract: Egr-1 is an inducible transcription factor that recognizes 9-bp target DNA sites via three zinc finger domains and activates genes in response to cellular stimuli such as synaptic signals and vascular stresses. Using spectroscopic and computational approaches, we have studied structural, dynamic, and kinetic aspects of the DNAscanning process in which Egr-1 is nonspecifically bound to DNA and perpetually changes its location on DNA. Our NMR data indicate that Egr-1 undergoes highly dynamic domain motions when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
167
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 93 publications
(174 citation statements)
references
References 58 publications
6
167
0
Order By: Relevance
“…1A). Our previous studies suggested that the interdomain dynamics could harness the rapid conformational switch between the search and recognition modes, thereby allowing Egr-1 to overcome the speedstability paradox (24,28). Our current work is based on a hypothesis that the balance between the search and recognition modes is a major determinant of the kinetic efficiency in target DNA search by ZF proteins.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1A). Our previous studies suggested that the interdomain dynamics could harness the rapid conformational switch between the search and recognition modes, thereby allowing Egr-1 to overcome the speedstability paradox (24,28). Our current work is based on a hypothesis that the balance between the search and recognition modes is a major determinant of the kinetic efficiency in target DNA search by ZF proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous NMR and computational investigations on nonspecific and specific DNA complexes of Egr-1 suggested that, while scanning DNA, Egr-1 undergoes the dynamic conformational equilibrium between the search and recognition modes (28). We consider the conformational ensemble involving three major states in the DNA-scanning process as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Functional asymmetry can be observed when identical domains perform distinct tasks: i) the zinc fingers of the Egr-1 transcription factor perform rapid scanning and stable recognition (Zandarashvili et al, 2012) and ii) histidine kinase receptor dimers possess either kinase or phosphatase activities (Moore and Hendrickson, 2012). Operational asymmetry arises when the symmetry of enzyme reaction cycles is broken, which can lead to evolutionary consequences (García-Bellido, 1996).…”
Section: Introductionmentioning
confidence: 99%